Pemanfaatan Aplikasi Desain Canva Sebagai Media Peningkatan Promosi Produk untuk UMKM di Desa Penyasawan - Rahmad Akbar; Dzulhijjah Yetti; Nurbit Nurbit; Harmi Yelmi; Yedi Sispurwanto; Indra Habibie; Andri Nofiar. Am; Nurkholis; Tri Kurniaty; Hafid, Burhan (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The advancement of digital technology has significantly transformed marketing strategies, especially for micro, small, and medium enterprises (MSMEs) in rural areas. This community service program was conducted in Penyasawan Village, Kampar Regency, aiming to improve the digital marketing capabilities of local culinary MSMEs through training in the use of the Canva design application. The main problems faced by the MSMEs in the village include limited knowledge of digital marketing, lack of design skills, and financial constraints to hire professional graphic designers. This program provided a practical solution by organizing a hands-on training session on how to create promotional materials such as posters, banners, and social media content using Canva. The training involved 20 MSME participants and was implemented through several stages: preparation, implementation, and monitoring-evaluation. The results showed an increase in participants' abilities to independently design effective promotional materials, which are expected to expand their market reach and increase product sales. This activity not only enhanced digital literacy among MSMEs but also supported the growth of the local economy through improved promotional strategies.